Exercise Training at MLSS Decreases Weight Gain and Increases Aerobic Capacity in Obese Zucker Rats - Almeida, J. A.; A. Petriz, B.; Gomes, C. P. C.; Araujo, R. C.; Pereira, R. W.; Franco, O. L. (International Journal of Sports Medicine, 2014)
This study aimed to identify the aerobic capacity enhancement and subsequent body weight (BW) status of obese Zucker rats (OZRs) after 4 weeks of treadmill running exercise at the maximal lactate steady state (MLSS). In addition to obese Zucker rats (OZRs), lean Wistar Kyoto rats (WKYs) were used, and both species were divided into control and exercise groups as follows: obese exercise (OZR-EX, n=5), obese control (OZR-CON, n=5), lean exercise (WKY-EX, n=5) and lean control (WKY-CON, n=5). The OZR and WKY exercise groups trained 5 days per week at 12.5 m.min−1 and 20 m.min−1, respectively. After 4 weeks of training, MLSS was ascertained to evaluate the animals’ aerobic capacity using 3 different velocities (12.5, 15 and 17.5 m.min−1 for OZRs and 25, 30 and 35 m.min−1 for WKYs). The MLSS of OZR-EX was identified at the velocity of 15 m.min−1, representing a 20% increase in aerobic capacity after the exercise program. The MLSS of WKY-EX was identified at 30 m.min−1 with a 50% increase of in aerobic capacity. Obese animals that exercised showed reduced weight gain compared to the non-exercise obese control group (p <0.05). Our results thus show that exercise training at MLSS intensity increased the aerobic capacity in both obese and non-obese animals and also reduced BW gain.
Keywords: obese Zucker rat; MLSS; lactate threshold; aerobic capacity; treadmill running; exercise Training